A logisztikai szektor dolgozóinak digitalizáció iránti motivációja a személyiségjegyek függvényében - Patrik Urbán (Competitio, 2026)
Digitalization has become a key driver of economic and organizational development, fundamentally transforming the operation of the logistics sector. In this process, it is especially important to understand what motivates employees working in logistics to adopt digitalization, and how their personality traits - primarily extraversion - affect their openness to technology. Based on a questionnaire measuring Eysenck’s personality dimensions, the findings show that employees have strong internal motivation to use digital tools and feel competent in applying the technology. Most employees do not see digitalization as an obligation, but rather as an opportunity for growth. The results also highlight that organizational and environmental factors influence the willingness to engage with digitalization. The main conclusion of the research is that for digital development projects to be successful, companies should not only ensure the basic technological conditions but also strengthen employees’ internal motivation, sense of competence, and psychological needs. JEL codes: O33, J24, D91, M54, D90